Intracranial tumors mimicking benign paroxysmal positional vertigo: A case series - Chen, Yuan Xing; Sun, Han Jun; Mu, Xue Tao; Jiang, Chao; Wang, Hui Bing; Zhang, Qing Hua; Qu, Yuan Yi; Li, Jian; Zhou, Ling Ling; Zhao, Long Zhu; Yu, Ning; Sun, Qing (Frontiers in Neurology, 2022)
Background A few intracranial lesions may present only with positional vertigo which are very easy to misdiagnose as benign paroxysmal positional vertigo (BPPV); the clinicians should pay more attention to this disease. Objectives To analyze the clinical characteristics of 6 patients with intracranial tumors who only presented with positional vertigo to avoid misdiagnosing the disease. Material and methods Six patients with intracranial tumors who only presented with positional vertigo treated in our clinic between May 2015 to May 2019 were reviewed, and the clinical symptoms, features of nystagmus, imaging presentation, and final diagnosis of the patients were evaluated. Results All patients presented with positional vertigo and positional nystagmus induced by the changes in head position or posture, including one case with downbeating nystagmus in a positional test, two cases with left-beating nystagmus, one case with apogeotropic nystagmus in a roll test, one case with right-beating nystagmus, and one case with left-beating and upbeating nystagmus. Brain MRI showed the regions of the tumors were in the vermis of the cerebellum, the fourth ventricle, the lateral ventricle, and the cerebellar hemisphere.